Cote d'Ivoire : Staff Report for the 2001 Article IV Consultation and Staff-Monitored Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The three-year arrangement under the Poverty Reduction and Growth Facility (PRGF) that was approved by the Executive Board of the IMF in March 1998 in support of Cote d'lvoire's adjustment efforts went off track after the first year. In the cocoa and coffee sectors, the measures that were supposed to accompany the liberalization process, such as the strengthening of producer organizations and the rehabilitation of rural infrastructure, were not fully implemented. Executive Directors welcomed the conclusion of discussions on a Staff-Monitored Program (SMP).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet